The predictive role of inflammation indices derived from complete blood count in severe COVID-19 patients: a study from the United Arab Emirates - Zeidan, Rouba Karen; Al-Bluwi, Najlaa; AlZubaidi, Hamzah; Awad, Manal; Hussein, Amal; AlHajjaj, Mohamed; Saddik, Basema (Frontiers in Medicine, 2025)
PurposeTo investigate the predictive effect and determine the cut-off values of complete blood count parameters in severe COVID-19 hospitalized patients in the United Arab Emirates.MethodsA retrospective observational analytical study analyzed data from 738 medical records of COVID-19 hospitalized patients across several healthcare centers in the United Arab Emirates between 29 January 2020 and 14 October 2021. Complete blood count ratios and indices on admission were evaluated for COVID-19 severity using receiver operating characteristic curves, sensitivity, and specificity.ResultsMain complete blood count-based ratios and indices significantly predicting severe COVID-19 were elevated ratios index (optimal cut-off point ≥3; AOR = 2.8, 95% CI: 1.77–4.42), systemic immune-inflammation index (≥1259.95; AOR = 2.4, 95% CI: 1.53–3.87), systemic inflammation response index (≥3.96; AOR = 2.9, 95% CI: 1.79–4.72), aggregate index of systemic inflammation (≥949.02; AOR = 2.3, 95% CI: 1.43–3.77), platelet-to-lymphocyte ratio (≥188.91; AOR = 2.2, 95% CI: 1.39–3.53), derived neutrophil-to-lymphocyte ratio (≥2.91; AOR = 3.0, 95% CI: 1.84–4.87), and neutrophil-to-lymphocyte ratio (≥6.01; AOR = 3.2, 95% CI: 1.98–5.12).ConclusionIdentifying hematological markers’ predictive effects and their cut-off values can aid healthcare providers in risk classification and the development of tailored treatment plans. It can also provide cheap, quick, and easy guidance for surveillance systems to lessen the impact of any future outbreaks.